Delta Flower Beetle Trigonopeltastes delta (Forster 1771) (Insecta: Coleoptera: Scarabaeidae : Cetoniinae : Tribe, Trichiini) - Brandon Jones; Andrea Lucky (EDIS)
The delta flower beetle, Trigonopeltastes delta (Forster), is a member of the scarab beetle family Scarabaeidae, in the subfamily Cetoniinae. This subfamily is commonly known as flower or fruit chafers because their diet consists mostly of decomposing fruits or pollen (Cave and Ratcliffe 2008). Trigonopeltastes delta belongs to the tribe Trichiini, which contains mostly flower-frequenting species. Although this species is commonly encountered where it occurs, many details of its life cycle and its potential economic importance remain poorly studied. Like many other cetoniines, the delta flower beetle has bright colors and distinctive patterns that distinguish it from other similar species. Includes: Introduction - Etymology and Synonymy - Distribution - Description and Life Cycle - Hosts - Economic Importance - Selected References. https://edis.ifas.ufl.edu/in1214